1997
DOI: 10.1128/aem.63.8.3225-3232.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of several factors on the heat-shock-induced thermotolerance of Listeria monocytogenes

Abstract: The influence of the temperature at which Listeria monocytogenes had been grown (4 or 37 degrees C) on the response to heat shocks of different durations at different temperatures was investigated. For cells grown at 4 degrees C, the effect of storage, prior to and after heat shock, on the induced thermotolerance was also studied. Death kinetics of heat-shocked cells is also discussed. For L. monocytogenes grown at 37 degrees C, the greatest response to heat shock was a fourfold increase in thermotolerance. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
2
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 46 publications
1
32
2
4
Order By: Relevance
“…(2009) observed that the highest homologous response for C. sakazakii BCRC 13988 cells was achieved after an exposure of 15 min at 47°C, such that the D 51 value was increased 2·5‐fold. This increase in thermotolerance is higher than the increase reported here (1·6 times), but it is still lower than other magnitudes reported (Pagán et al. 1997; Cebrián et al.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…(2009) observed that the highest homologous response for C. sakazakii BCRC 13988 cells was achieved after an exposure of 15 min at 47°C, such that the D 51 value was increased 2·5‐fold. This increase in thermotolerance is higher than the increase reported here (1·6 times), but it is still lower than other magnitudes reported (Pagán et al. 1997; Cebrián et al.…”
Section: Discussioncontrasting
confidence: 77%
“…The development of resistance to heat after a heat shock is a widely observed phenomenon (Mackey and Derrick 1987; Linton et al. 1990; Pagán et al. 1997; Jørgensen et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the induced thermotolerance in the heat‐resistant strain was only based on a higher capacity of heat damage repair as the survival curve of the heat‐shocked cells obtained after recovery in selective conditions was similar to that obtained with nonheat‐shocked cells. Both the increase in intrinsic heat resistance and in capacity of heat damage repair are two general mechanisms of bacterial heat resistance increase under the influence of a heat shock (Pagán et al. 1997; Mackey 2000).…”
Section: Discussionmentioning
confidence: 99%
“…2005), there is very little information on the influence of environmental factors affecting heat resistance of this micro‐organism. Microbial heat resistance varies greatly among different species, and also it might be strongly influenced by many environmental factors such as those related to the treatment conditions: treatment medium pH, water activity or the occurrence of nonisothermal heating lag phases (Hansen and Riemann 1963; Pagán et al. 1997; Hassani et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation